2005
DOI: 10.1111/j.1439-0523.2004.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to anthracnose caused by Colletotrichum capsici in Capsicum

Abstract: Inheritance of resistance to anthracnose caused by Colletotrichum capsici in Capsicum P . P a kd eeva ra po rn 1 , S. W asee 2 , P . W . J . T ay lo r 3 and O . M on gk ol po rn 4 , 5 AbstractInheritance of resistance to anthracnose caused by Colletotrichum capsici (Syd.) Butler & Bisby was studied in interspecific Capsicum populations derived from a cross between a Thai elite cultivar Capsicum annuum L. ÔBangchangÕ and a resistant line C. chinense Jacq. ÔPBC932Õ. The resistance was assessed by measuring lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
105
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 9 publications
3
105
0
8
Order By: Relevance
“…Kanchana-Udomkan et al (2004) found that fruit size does not affect the development of the disease, and unripe fruit of C. chinense were more susceptible to anthracnose caused by C. gloeosporioides than ripe fruit. Pakdeevaraporn et al (2005) and Mahasuk et al (2009a) showed that different genes control resistance to anthracnose in unripe and ripe fruit, which is extremely significant for Capsicum breeding seeking resistance to anthracnose. Mongkolporn et al (2010) also observed different reactions caused by the stage of development of Capsicum spp.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Kanchana-Udomkan et al (2004) found that fruit size does not affect the development of the disease, and unripe fruit of C. chinense were more susceptible to anthracnose caused by C. gloeosporioides than ripe fruit. Pakdeevaraporn et al (2005) and Mahasuk et al (2009a) showed that different genes control resistance to anthracnose in unripe and ripe fruit, which is extremely significant for Capsicum breeding seeking resistance to anthracnose. Mongkolporn et al (2010) also observed different reactions caused by the stage of development of Capsicum spp.…”
mentioning
confidence: 99%
“…For resistance to C. gloeosporioides, inheritance was described as overdominant or partially dominant (Park et al, 1990a). The presence of a recessive gene controlling anthracnose resistance has also been described in Capsicum chinense (Pakdeevaraporn et al, 2005). Voorrips et al (2004) used quantitative trait loci (QTL) mapping and identified a highly significant main QTL with major effect on three evaluated traits (frequency of infection, lesion true diameter and overall diameter of lesion) after the inoculation of C. gloeosporioides in plants from crosses between Capsicum annuum and C. chinense.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Asian Vegetable Research Development Center (AVRDC) identified, in 1997 and in 1999, the main sources of anthracnose resistance in Capsicum plants for C. baccatum and C. chinense (Pakdeevaraporn et al, 2005). Since then, several researchers have used these genotypes in Capsicum breeding programs for resistance to anthracnose.…”
Section: Exp12 -Resistance Assessment To Anthracnosementioning
confidence: 99%
“…yield loss (Pakdeevaraporn et al, 2005). Typical anthracnose symptoms on chilli fruit include sunken necrotic tissues, with concentric rings of acervuli.…”
mentioning
confidence: 99%